2018
DOI: 10.23822/eurannaci.1764-1489.41
|View full text |Cite
|
Sign up to set email alerts
|

Dog allergy: can a prevalent or exclusive sensitization to Can f 5 be considered a lucky or negative event in “real life”?

Abstract: Recent studies have shown the increasing relevance of allergic sensitization to Can f 5 (a prostatic kallikrein), which is an androgen-regulated protein expressed in the prostate and detectable only in male dogs. Can f 5 can be a prevalent or exclusive sensitizing agent in a considerable percentage of dog-allergic patients. Its specific allergenic characteristics are able to induce possible negative as well as positive clinical effects in individuals sensitized to dogs. In the present article we pointed out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…sensitized patients or pet-sensitized individuals living in areas with a high pet ownership (6)(7)(8). The peculiar characteristics of Can f 5, in highly or exclusive sensitized patients, can determine positive and negative actions which must be carefully evaluated by allergists managing such patients (9,10). In Italy, data on the frequency of Can f 5 as sensitizing agent in dog allergic individuals are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…sensitized patients or pet-sensitized individuals living in areas with a high pet ownership (6)(7)(8). The peculiar characteristics of Can f 5, in highly or exclusive sensitized patients, can determine positive and negative actions which must be carefully evaluated by allergists managing such patients (9,10). In Italy, data on the frequency of Can f 5 as sensitizing agent in dog allergic individuals are lacking.…”
mentioning
confidence: 99%
“…Possible topics associated with a prevalent or exclusive allergic sensitization to Can f 5. Adapted from(10). (The picture of the dog "Charlie" 2001 -2017 is property of GL).…”
mentioning
confidence: 99%
“…Moreover, our Italian multicenter study has shown that a prevalent exposure to a male dog represents a risk factor for the presence of Can f 5 monosensitization (56). The results of this study emphasize the need of an adequate diagnosis and management of patients suffering from dog allergy, especially those with relevant clinical symptoms following dog exposure in order to prevent systemic SPH (57).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 57%
“…In addition to this probable effect on the efficacy of DAI, patients suffering from this specific sensitization might experience either favourable or unfavourable clinical conditions in "real life". 26 (Table 1).…”
Section: Prevalent Sensitization To Major Dog Allergens (Can F 2 and Can F 2) Or Multiple Sensitization To Other Allergens Of Furry Animamentioning
confidence: 99%
“…-Can f 5 should not cross-react to other mammalian "pan-allergens" belonging to albumins or lipocalins family. 26 Possible reduction of the occurrence of dog allergen «ubiquity» and consequent effects. -To the best of our knowledge, no studies have previously demonstrated a passive transport of Can f 5 in dog-free indoor environments.…”
Section: Possible Favourable Conditionsmentioning
confidence: 99%